2018
DOI: 10.1161/jaha.118.009205
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Nuclear Translocator in Vascular Smooth Muscle Cells Is Required for Optimal Peripheral Perfusion Recovery

Abstract: BackgroundLimb ischemia resulting from peripheral vascular disease is a common cause of morbidity. Vessel occlusion limits blood flow, creating a hypoxic environment that damages distal tissue, requiring therapeutic revascularization. Hypoxia‐inducible factors (HIFs) are key transcriptional regulators of hypoxic vascular responses, including angiogenesis and arteriogenesis. Despite vascular smooth muscle cells’ (VSMCs’) importance in vessel integrity, little is known about their functional responses to hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…28 Although our data did not demonstrate any variation in HIF-1α and FGF2 mRNA expression, previous studies indicated that the loss of hypoxic signals in vascular SMC impaired the ability of mice to recover from ischemia following femoral artery ligation. Borton et al 29 have reported that the deletion of the HIF-β subunit in SMC altered SMC proliferation and migration as well as compromised limb reperfusion. Others have shown that FGF2 is an important element in the arteriogenic response of SMC.…”
Section: Discussionmentioning
confidence: 99%
“…28 Although our data did not demonstrate any variation in HIF-1α and FGF2 mRNA expression, previous studies indicated that the loss of hypoxic signals in vascular SMC impaired the ability of mice to recover from ischemia following femoral artery ligation. Borton et al 29 have reported that the deletion of the HIF-β subunit in SMC altered SMC proliferation and migration as well as compromised limb reperfusion. Others have shown that FGF2 is an important element in the arteriogenic response of SMC.…”
Section: Discussionmentioning
confidence: 99%